2018
DOI: 10.1097/bot.0000000000001235
|View full text |Cite
|
Sign up to set email alerts
|

Dogs and Orthopaedic Injuries: Is There a Correlation With Breed?

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
1
5
1
Order By: Relevance
“…Unique to our study, however, was the finding that the age group at time of injury correlated with specific dog breeds, in that pit bulls were statistically less likely to inflict harm on infants and preschool children. Nonetheless, the most likely breed to be implicated in attacks in our data set was pit bull or pit bull mix, similar to several prior studies 2,16–22 . However, contrasting reports suggest that pit bulls may be misidentified disproportionately compared with other breeds 23–36 …”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Unique to our study, however, was the finding that the age group at time of injury correlated with specific dog breeds, in that pit bulls were statistically less likely to inflict harm on infants and preschool children. Nonetheless, the most likely breed to be implicated in attacks in our data set was pit bull or pit bull mix, similar to several prior studies 2,16–22 . However, contrasting reports suggest that pit bulls may be misidentified disproportionately compared with other breeds 23–36 …”
Section: Discussionsupporting
confidence: 80%
“…A possible explanation for peak attack incidence falling in the warmer months is likely related to dogs being put outside and children playing outside once it is warm enough to do so, thus increasing the chance of interaction. Although some other studies have demonstrated that pit bull breed was correlated with higher incidence of complex injury requiring surgical repair, our analysis found no statistically significant difference in surgical management or location of surgical management (proxies for severity) based on dog breed 2,16,19,20,34 . Similarly, a study by Gurunluoglu et al 35 did not find an association between need for more advanced reconstructive techniques and dog breed.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Studies have shown that one third of patients with a dog bite injury required orthopedic treatment. 15 Yet, there is little published data regarding the appropriate utilization of imaging among this patient population. We hypothesized that imaging is overused in the initial workup of these patients.…”
mentioning
confidence: 99%